Armenian spiritual centers and their cultural activities in Georgia in the 14-15 th centuries. - Melikyan, Lilit (History and Culture, 2022)
The article is devoted to the coverage of the spiritual and cultural life of the Armenian diaspora in Georgia in the 14-15th centuries. The study is based on the manuscript sources and documents of Matenadaran named after Mesrop Mashtots. An attempt is made to present the activities of the Armenian spiritual centers, the relations between the Armenian scriptoriums in Georgia and in Armenia, to clarify the personality and activities of the scripters and miniaturists. Special attention was paid to the coverage of the history of the first Armenian school operating in Tipghis.
Keywords: Georgia; Saint George Church; school; scriptorium; miniaturist; scripter; colophon; Krtsanis; Pashivank; Bethlehem Church